Crescimento de monocristais de arsenito de galio (GaAs) pelo metodo Bridgman. - Oliveira, Clovis Eduardo Mazzotti de, 1962- (1989)
Orientadores: Alaide Pelegrini Mammana, Mauro Monteiro Garcia de Carvalho